Students' and Teachers' Perceptions of Bullying in High Schools - Syafriwana, Syafriwana (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study aims to explore students' and teachers' perceptions of bullying in high schools and their responses to bullying cases. Using a qualitative approach with a case study method, the study involved 20 students and 10 teachers from two schools in city X, selected through purposive sampling. Data were collected through semi-structured interviews and focus group discussions (FGD), then analyzed using thematic analysis. The results indicate a difference in perceptions between students and teachers. Students tend to view verbal bullying as part of